1, 3‐Bis(aryloxy)propan‐2‐ols as potential antileishmanial agents. (28th June 2017) - Lavorato, Stefânia N.; Duarte, Mariana C.; Lage, Daniela P.; Tavares, Carlos A. P.; Coelho, Eduardo A. F.; Alves, Ricardo J.
Abstract : We describe herein the synthesis and antileishmanial activity of 1, 3‐bis(aryloxy)propan‐2‐ols. Five compounds (2, 3, 13, 17, and18 ) exhibited an effective antileishmanial activity against stationary promastigote forms of Leishmania amazonensis (IC50 < 15.0 μm ), and an influence of compound lipophilicity on activity was suggested. Most of the compounds were poorly selective, as they showed toxicity toward murine macrophages, except17 and18, which presented good selective indexes (SI ≥ 10.0). The five more active compounds (2, 3, 13, 17, and18 ) were selected for the treatment of infected macrophages, and all of them were able to reduce the number of internalized parasites by more than 80%, as well as the number of infected macrophages by more than 70% in at least one of the tested concentrations. Altogether, these results demonstrate the potential of these compounds as new hits of antileishmanial agents and open future possibilities for them to be tested in in vivo studies. Abstract : The antileishmanial activity of several 1, 3‐bis(aryloxy)propan‐2‐ols is described for the first time. Compounds2, 3, 13, 17, and18 exhibited an effective antileishmanial activity against stationary promastigote forms of Leishmania amazonensis (IC50 < 15.0 μm ) and they were able to reduce the parasite burden in L. amazonensis ‐infected macrophages by more than 70% in tested concentrations.